2010
DOI: 10.1111/j.1399-0012.2009.01151.x
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of the donor pancreas for whole pancreas and islet transplantation

Abstract: Whole pancreas and islet cell transplantation are both reliant upon the procurement and preservation of a high quality donor pancreas for a successful outcome. In the climate of a reducing donor pool it is imperative that donor optimization, meticulous surgical retrieval and evidence based methods of preservation are practiced to ensure optimal graft quality. Moreover expanded criteria donors and novel methods of pancreas preservation have the potential to expand the number of usable grafts and increase the av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 204 publications
(225 reference statements)
0
14
0
1
Order By: Relevance
“…This acidosis kills cells by inducing lysosomal instability, activating enzymes, disrupting binding of transition ions to carrier proteins and altering mitochondrial properties. 12 Our results found that prolonged cold preservation affected exocrine acinar cells by little necrotic changes and abundant apoptotic proportions. On the other hand, islets viability inside the tissue was unaffected.…”
Section: Discussionmentioning
confidence: 57%
“…This acidosis kills cells by inducing lysosomal instability, activating enzymes, disrupting binding of transition ions to carrier proteins and altering mitochondrial properties. 12 Our results found that prolonged cold preservation affected exocrine acinar cells by little necrotic changes and abundant apoptotic proportions. On the other hand, islets viability inside the tissue was unaffected.…”
Section: Discussionmentioning
confidence: 57%
“…Today, insulin-dependent patients rely on daily insulin injections. Transplantation of isolated islets from cadavers is problematic due to donor scarcity (about 6000 islets/kg of body weight are required [13][14][15]), and is only applicable to certain forms of diabetes; in addition, transplantation has met with limited success due to restricted engraftment survival [16][17][18][19]. A promising approach relies on devising unlimited in vitro generation of insulin- Table 1.…”
Section: Towards Cell Replacement Therapymentioning
confidence: 99%
“…The vast majority of islets for transplantation derive from donors who have been declared brain dead (Grundfest-Broniatowski and Novick 1986;Ridgway et al 2010;Shapiro et al 2000Shapiro et al , 2006. Jung et al (2007) have shown that islet yield from living donors is higher compared to cadaveric donors, and cerebrovascular stroke as cause of death and intracranial haemorrhage as mechanism of death are significantly associated with unsuccessful islet isolation (Takita et al 2010).…”
Section: Donor and Retrieval Factorsmentioning
confidence: 99%
“…Conversely, outcomes are substantially worsened for nonheart beating donors (Jung et al 2007;Kenmochi et al 2008). Donors who have poor glucose control during their intensive care unit admission are less likely to provide a successful islet yield, as are those who require high levels of inotropes to attempt to maintain blood pressure (Brandhorst et al 1994(Brandhorst et al , 1995Lakey et al 1995;Ridgway et al 2010). …”
Section: Donor and Retrieval Factorsmentioning
confidence: 99%
See 1 more Smart Citation